Sufficiency economy philosophy and sustainable development for public administration - Ayuthaya, Chirayu Isarangkun Na (2011)
The conflict and violence ravaging the world have drawn attention to flaws in the prevailing world development model. Thailand had been doing well according to that model, but it suffered greatly in the East Asian economic crisis of 1997. Out of that experience, it moved to adopt a new model, described as Sufficiency Economy Philosophy (or SEP), that was proposed by the King. This model teaches the need to maintain fiscal discipline and rethink the role of the state, with the people in each local community determining their own sustainable development with an appropriate balance of economic, societal, environmental, and cultural objectives.
Keywords: Sustainable development -- Thailand; Sustainable urban development -- Thailand; Sufficiency Economy Philosophy (SEP); International cooperation with sustainable development